Sharia Financial Literacy, Religiosity, and MSME Loan Decisions at BSI in Genteng District - Dita Nazillatul Hidayah; Rachmania Nurul Fitri Amijaya; Moch. Shulthoni (Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Purpose - The purpose of this study is to examine the effect of Islamic financial literacy and religiosity on MSMEs’ decisions to apply for People’s Business Credit (KUR) financing in Banyuwangi Regency. Method - To achieve this purpose, the study uses a quantitative approach with a logistic regression analysis model to test the hypotheses. The number of respondents in this study was 100 MSME owners who had been running their businesses for at least 6 months and were located in Genteng District, Banyuwangi Regency. This study aims to determine the influence of Islamic financial literacy and religiosity on the decision to apply for a loan at Bank Syariah Indonesia's KUR program. Result - The findings of this research show that Islamic financial literacy has a positive effect on the decision to apply for KUR, and religiosity also has a significant positive effect on KUR application decisions among MSMEs in the area studied. Implication - The findings imply that improving Islamic financial literacy and strengthening sharia-based values can increase MSMEs’ willingness to access KUR financing. Therefore, Islamic banks and policymakers should prioritize financial education and value-based outreach to enhance MSME access to sustainable capital and support local economic development. Originality - This study is original in that it simultaneously examines Islamic financial literacy and religiosity as determinants of MSMEs’ decisions to apply for sharia-based KUR financing, using a logistic regression approach in a regional MSME context. Furthermore, there is a specific research gap, namely the limited empirical evidence that comprehensively analyzes how Islamic financial literacy and religiosity influence MSMEs' actual decisions to apply for Sharia-based KUR financing at the district level, particularly using a binary outcome-based dependent variable design (apply or not apply). Most previous studies have focused more on interests, perceptions, or preferences, rather than on quantitatively observed real-world decisions. Keywords: Islamic financial literacy, religiosity, Sharia KUR, MSME financing,, logistic regression, Bank Syariah Indonesia, Banyuwangi